Pengaruh Pemupukan terhadap Perubahan Morfofisiologi Dua Varietas Padi pada Kondisi Cekaman Rendaman - ., Gribaldi; Hasmeda, Merry; Hayati, Renih (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2014)
ABSTRACTSubmergence tolerance is plant adaptation to anaerobic or hypoxia condition without significant damage.  Changes in morphophysiological characters of rice plant are often related to the plant adaptation to submergence stress.  Fertilization might affect  plant morphophysiological changes under submergence stress. The objective of this research was to study the effect of rice varieties and fertilizer application on the growth and morphophysiological changes under submergence stress. The experiment was arranged in factorial completely randomized block design with six replications. The first factor was rice varieties consisted of Inpara 5 (V1) and IR64 (V2), while the second factor was fertilizer application consisted of  without  fertilization (P0) and with fertilizer application (P1). Submergence stress was applied on 28 days old seedlings for 7 days.  The results showed that fertilizer application increased aerenchyma formation and plant N content of both IR64 and Inpara 5 varietes.  Inpara 5 variety had higher relative chlorophyll content, relative carbohydrate content, and relative plant dry weight thant IR64 variety at 7 days after submergence stress.    Keywords: fertilization, morphophysiology, submergence stress, tolerance